A Versatile Method for Uniform Dispersion of Nanocarbons in Metal Matrix Based on Electrostatic Interactions - Li, Zan; Fan, Genlian; Tan, Zhanqiu; Li, Zhiqiang; Guo, Qiang; Xiong, Dingbang; Zhang, Di (Nano-Micro Letters, 2015)
Realizing the uniform dispersion of nanocarbons such as carbon nanotube and graphene in metals, is an essential prerequisite to fully exhibit their enhancement effect in mechanical, thermal, and electrical properties of metal matrix composites (MMCs). In this work, we propose an effective method to achieve uniform distribution of nanocarbons in various metal flakes through a slurry-based method. It relies on the electrostatic interactions between the negatively charged nanocarbons and the positively charged metal flakes when mixed in slurry. For case study, flake metal powders (Al, Mg, Ti, Fe, and Cu) were positively charged in aqueous suspension by spontaneous ionization or cationic surface modification. While nanocarbons, given examples as carboxylic multi-walled carbon nanotubes, pristine single-walled carbon nanotube, and carbon nanotube–graphene oxide hybrid were negatively charged by the ionization of oxygen-containing functional groups or anionic surfactant. It was found that through the electrostatic interaction mechanism, all kinds of nanocarbons can be spontaneously and efficiently adsorbed onto the surface of various metal flakes. The development of such a versatile method would provide us great opportunities to fabricate advanced MMCs with appealing properties.